Análise da eficiência de elementos de proteção solar em relação ao sombreamento e a iluminação natural estudo de caso: salas de aula do campus I da UFPB - Marques, Matheus Peixoto de Paula (2012)
This work addresses topics such as shading devices, shading and daylighting. It aims at verifying the efficiency of shading devices found classroom buildings at UFPB's campus I, with respect to shading and daylighting. The results of the research focus in the diagnosis of the solutions in the case study, by using three dimensional models (3D) and computer simulation. The digital models were constructed from data collected in field surveys. The computer programs used were the Solar Tool, Ecotect and Daysim. In parallel, we investigated a set of hypothetical situations, considering all the solutions found in the survey, in order to identify the performance of the solutions in other orientation facade. The evaluation of the models was made from performance measures such as the percentage of shading, percentage of sky visibility and useful daylight illuminances (UDI). From the results, we observed that: a) south-oriented façades with unprotected openings allow for environments with higher levels and better distribution of natural lighting; b) a large part of the orientation facade analyzed, except in the northwest and east, more than 50% of the samples obtained a good performance of daylighting; c) the percentage of shading is not enough to say whether an element of sunscreen is effective or not, which can generate misleading conclusions when used alone; d) the correlation of the performance of daylighting and performance of shading with the percentage of sky visibility, showed that for every orientation facade there is an optimal ratio between the percentage of shading and the percentage of sky visibility, and for the facade analyzed, the values of these measures are generally around 88.7% of shading of the opening and 8.1% of sky visibility.